1969
DOI: 10.1128/aem.18.3.376-386.1969
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Study of Water-Softener Resins

Abstract: Microbial identification using effluents backflushed from exhausted urban and rural tank resins and cleaned resins containing the sulfonated copolymer of styrene and divinylbenzene (SDB) were completed, along with microbial assessment of the concentrated stock salt brine. Forty-four different bacterial and fungal genera were identified. Extensive biochemical and animal virulence tests completed on one of the six bacterial salt brine isolates indicated a pathogenic staphylococcal strain. The retention of Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Mechanical plumbing equipment located in mechanical spaces and “upstream” of the main building piping network (Table 1) must be considered. Bacterial growth, including pathogens, has been associated with this equipment and with subsequent disease cases (Bédard et al, 2016; Borella et al, 2004; Garrison et al, 2016; Stamm, Engelhard, & Parsons, 1969). Volume stored in the devices must be overturned, which can be difficult because of nonideal flow through them (e.g., water heaters; Hawes et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical plumbing equipment located in mechanical spaces and “upstream” of the main building piping network (Table 1) must be considered. Bacterial growth, including pathogens, has been associated with this equipment and with subsequent disease cases (Bédard et al, 2016; Borella et al, 2004; Garrison et al, 2016; Stamm, Engelhard, & Parsons, 1969). Volume stored in the devices must be overturned, which can be difficult because of nonideal flow through them (e.g., water heaters; Hawes et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The potential health hazards of microbial contamination in fluids associated with dialysis procedures in hemodialysis and peritoneal dialysis centers have previously been related (15,16,20,25,27,29,32) to a variety of causal factors including: (i) high levels of gram-negative bacteria or associated endotoxins in source waters used to prepare dialysis fluids; (ii) the efficacy of various types of water treatment systems (i.e., softening, deionization, reverse osmosis) in harboring or reducing microbial contaminants or in removing endotoxins; (iii) the effectiveness of disinfection procedures in eliminating or preventing colonization of filters, membranes, and modules in water treatment systems or piping in fluid distribution systems; and (iv) the problems of specific machine designs associated with failure of disinfection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of the water used to prepare dialysis fluids at these various centers varied from no treatment to softening, deionization, and/or reverse osmosis (Table 1). It has been shown that softeners and deionizers allow for the rapid growth of gram-negative bacteria especially in the absence of residual chlorine (14,19). Although the process of reverse osmosis tends to produce water that is low in bacteriological content, in the absence of residual chlo-rine microorganisms can readily multiply in the distribution system downstream from the membrane.…”
Section: Discussionmentioning
confidence: 99%